Penerapan Solar Home System Berbasis Baterai Lithium sebagai Solusi Transisi Energi Terbarukan - Herman HR; Muhammad Yusuf Yunus; Naomi Lembang (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The dependence of the electrical power system on fossil fuels can lead to various environmental problems and pose threats to energy sustainability. Approximately 81% of the electricity supply still comes from fossil fuels, which can cause high carbon emissions and supply instability due to limited fossil fuel reserves. These problems can be overcome by implementing Solar Home Systems (SHS) as an environmentally friendly solar-based renewable energy solution. This research was conducted experimentally at the Energy Conversion Laboratory, Ujung Pandang State Polytechnic. Solar Home Systems (SHS) require batteries to store energy produced by photovoltaics, where the energy captured by the panels is converted through a chemical process into electrical energy. The batteries used are lithium batteries, which have high energy density and a longer lifespan. The energy source has a capacity of 50 Wp stored in 24 lithium batteries, which can supply energy for a load of 50 watts. Considering these factors, an increased capacity is necessary if longevity is desired, along with the addition of instruments to measure the battery percentage for more precise readings.